Determination of ergocalciferol in human plasma after Diels-Alder derivatization by LCâMS/MS and its application to a bioequivalence study - Pritesh Contractor; Abhishek Gandhi; Gajendra Solanki; Priyanka A. Shah; Pranav S. Shrivastav (Elsevier, 2017)
An accurate, sensitive and selective method is developed for determination of ergocalciferol (vitamin D2) in human plasma using LCâMS/MS. After liquid-liquid extraction with n-hexane, ergocalciferol was derivatized by reacting with 4-phenyl-1,2,4-triazoline-3,5-dione (PTAD), a strong dienophile based on Diels-Alder reaction. Ergocalciferol and its deuterated internal standard, ergocalciferol-d6, were analyzed on X Select CSH C18 (100Â mmÃ4.6Â mm, 2.5Â Âµm) column using acetonitrile and 0.1% (v/v) formic acid in water containing 0.14% methylamine within 6.0Â min under gradient elution mode. Tandem mass spectrometry in positive ionization mode was used to quantify ergocalciferol by multiple reaction monitoring (MRM). Entire data processing was done using Watson LIMSâ¢ software which provided excellent data integrity and high throughput with improved operational efficiency. The major advantage of this method includes higher sensitivity (0.10Â ng/mL), superior extraction efficiency (â¥83%) and small sample volume (100Â ÂµL) for processing. The method was linear in the concentration range of 0.10â100Â ng/mL for ergocalciferol. The intra-batch and inter-batch accuracy and precision (% CV) values varied from 97.3% to 109.0% and 1.01% to 5.16%, respectively. The method was successfully applied to support a bioequivalence study of 1.25Â mg ergocalciferol capsules in 12 healthy subjects. Keywords: Ergocalciferol, Diels-Alder reaction, 4-phenyl-1,2,4-triazoline-3,5-dione, LCâMS/MS, Human plasma